2020
DOI: 10.1016/j.mayocp.2020.07.009
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences in Mortality Rates and Underlying Conditions for COVID-19 Deaths in England and Wales

Abstract: Objective: To address the issue of limited national data on the prevalence and distribution of underlying conditions among COVID-19 deaths between sexes and across age groups. Patients and Methods: All adult (18 years) deaths recorded in England and Wales (March 1, 2020, to May 12, 2020) were analyzed retrospectively. We compared the prevalence of underlying health conditions between COVID and noneCOVID-related deaths during the COVID-19 pandemic and the age-standardized mortality rate (ASMR) of COVID-19 compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
34
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 27 publications
5
34
0
Order By: Relevance
“…To our knowledge, this is one of the first studies to investigate sex differences in COVID-19 in important CV outcomes and the degree of systemic inflammation after adjustment for comorbidities [ 6 , 13 ]. These findings support differences in sex-specific responses, but suggest that these differences are likely independent of common cardiovascular comorbidities, as has previously been advocated but not well studied [ 8 , 14 , 15 ].…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…To our knowledge, this is one of the first studies to investigate sex differences in COVID-19 in important CV outcomes and the degree of systemic inflammation after adjustment for comorbidities [ 6 , 13 ]. These findings support differences in sex-specific responses, but suggest that these differences are likely independent of common cardiovascular comorbidities, as has previously been advocated but not well studied [ 8 , 14 , 15 ].…”
Section: Discussionsupporting
confidence: 85%
“…Men have consistently higher unadjusted and adjusted mortality from COVID-19 compared to women as reported by various international agencies and prior literature [ [3] , [4] , [5] , [6] ]. This sex difference in mortality may be related to greater underlying comorbidities in men compared to women, such as hypertension and CVD, which have been linked to increased severity of COVID-19 [ 5 , 7 , 8 ]. In addition, two factors that may contribute to mortality in COVID-19 include myocardial injury defined by troponin elevation, and increased systemic inflammation, both independently associated with in-hospital mortality [ 1 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Any additional delays due to the backlog will lead to increased mortality. Of course, these are approximate figures and does not account for excess mortality due to COVID-19 [37].…”
Section: Discussionmentioning
confidence: 99%
“…Similar studies in other countries have reported that COVID-19 was a very significant cause of death in Europe during the first wave of the pandemic, e.g., in England, data from the Office for National Statistics showed that COVID-19 was to blame for one-quarter of all deaths in April 2020 ( n = 33,841, 26.7% of the total deaths) 1 ( 5 ), and the role of comorbidities was also explored in the UK data ( 6 ).…”
Section: Introductionmentioning
confidence: 99%